The Effect Of Distribution, Digital Marketing And Consumers On Interest In Buying Korean Music Album In Students - Yusnidar, Cut; Boihaki, Boihaki; Isnaini, Teuku; Azzuhra, Muslimah (Dharmas Education Journal (DE_Journal), 2023)
This study aims to determine "The Influence of Distribution, Digital Marketing and Consumer Attraction on Students' Interest in Buying Korean Music Albums (Study on Korean Music Fans in the Sigli Area, Pidie Regency)". Where the independent variables are Distribution (X1), Digital Marketing (X2) and Attractiveness (X3), and Purchase Interest (Y) as the dependent variable. The population in this study were students who are fans of Korean Music in the Sigli Area, Pidie Regency. Then the Simple Random Sampling method is used, namely the sampling of members of the population is done randomly without regard to the existing strata in the population. Based on the research results, the regression equation is obtained: Y = 2.028 + 0.316 X1 + 0.232 X2 + 0.415 X3. Based on the results of the analysis above, it can be concluded that of the three variables studied, it turns out that the consumer attractiveness variable (X3) has the most dominant influence of 41.5% on buying interest (Y) Korean music albums for Korean music fans in the Sigli area, District Pidie. The influence between the dependent and independent variables, namely each distribution variable (X1), digital marketing (X2) and consumer attractiveness (X3) on buying interest (Y) Korean music albums for Korean music fans in the Sigli area, Pidie Regency with a correlation index of 92.1% This means the relationship is very strong.